Peluang dan Tantangan Model Pembelajaran Small Group Discussion dalam Pendidikan Agama Islam (PAI) - Aryani, Wiwik Dyah; Badruzaman, Tjetjep Ismail; Maulana, Muhammad Rizal; Assyyah, Getta Sitti; Fauzi, Wildi Ahmad; Solihah, Rika; Fitriani, Dwi Awaliyah (Penerbit Widina, Widina Media Utama, 2025)
This study aims to critically examine the application of the Small Group Discussion (SGD) model in Islamic Religious Education (PAI) and to evaluate the opportunities and challenges associated with its implementation. The central issue addressed is the extent to which SGD contributes to improving the quality of PAI learning, encompassing the cognitive, affective, and psychomotor domains of students. This research employs a qualitative approach through a literature study method, analyzing and synthesizing findings from various previous empirical studies related to the use of SGD in educational settings. The review reveals that SGD significantly enhances student engagement, content comprehension, critical thinking skills, and the development of social attitudes such as tolerance and interpersonal communication. However, several challenges are identified, including the dominance of certain group members, limited discussion time, and variations in student capabilities, which may hinder the effectiveness of the method. The study concludes that SGD is a pedagogically effective and contextually relevant approach for Islamic education, provided that teachers play an active role as facilitators and the implementation is carefully designed.ABSTRAKPenelitian ini bertujuan untuk mengkaji secara mendalam penerapan model pembelajaran Small Group Discussion (SGD) dalam Pendidikan Agama Islam (PAI), serta mengevaluasi peluang dan tantangan yang dihadapi dalam pelaksanaannya. Permasalahan utama yang diangkat adalah sejauh mana model SGD mampu meningkatkan kualitas pembelajaran PAI, yang mencakup aspek kognitif, afektif, dan psikomotorik peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka, yaitu menganalisis dan menelaah temuan dari sejumlah hasil penelitian sebelumnya yang relevan dengan implementasi SGD dalam konteks pembelajaran PAI. Hasil kajian menunjukkan bahwa model SGD memberikan kontribusi nyata terhadap peningkatan partisipasi aktif siswa, pemahaman materi ajar, keterampilan berpikir kritis, serta penguatan sikap toleransi dan kemampuan komunikasi antarpeserta didik. Namun demikian, ditemukan pula sejumlah tantangan seperti dominasi diskusi oleh anggota tertentu, keterbatasan waktu, serta variasi kemampuan siswa yang dapat menghambat efektivitas diskusi. Kesimpulannya, SGD merupakan strategi pembelajaran yang efektif dan kontekstual dalam pendidikan agama, asalkan didukung oleh peran aktif guru sebagai fasilitator dan desain pelaksanaan yang matang